The Effect of System Quality, Information Quality, and Service Quality on User Satisfaction in the ELMAD Application in MAN 1 Malang City - Utomo, Giemza Bagus Muji; Ardianto, Yusaq Tomo; Sisharini, Nanik (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This research was conducted to find out how system quality, information quality, service quality, and ELMAD user satisfaction at MAN 1 Kota Malang. The quality of the information system in the ELMAD application system is the ability of the system itself, which is how much the information technology system is reliable and in accordance with the needs and expectations of its users. It can be said that users believe that the ELMAD application information system that is used is running well, they will be satisfied and feel the benefits of the information system. The population of this research is class XI students of IPS MAN 1 Kota Malang for the odd semester 2023 academic year with a total of 102 students. The sampling method used is the census method with active class stratified criteria and uses the K13 curriculum. For the sampling technique using non-probability sampling (not random). The results of this study indicate that system quality, information quality, service quality have a significant positive effect on user satisfaction of the ELMAD application at MAN 1 Malang City. The results of this study are implemented on system quality, information quality and service quality in the ELMAD application at MAN 1 Malang City which has been going well, but still needs to be improved in the use of the ELMAD application such as providing training to users in implementing a good ELMAD application, so that users maximize the operation of the application.